ANALISIS SIFAT KIMIA DAN DEKOMPOSISI TERMAL MODEL VYAZOVKIN SUTRA JAGUNG DENGAN PROSES PIROLISIS PADA LAJU PEMANASAN 40 O C/MENIT : ANALYSIS OF CHEMICAL PROPERTIES AND THERMAL DECOMPOSITION OF THE VYAZOVKIN MODEL OF CORN SILK BY PYROLYSIS PROCESS AT A HEATING RATE OF 40 O C/MINUTE - Citrakara Upendra Sneha Bandhana Kusuma Himawan; Rahmad, Hadi; Mutiara Bahtiar, Ahmad Dony (Jurnal Teknik Mesin, 2022)
Increasing levels of carbon dioxide (CO) in the atmosphere in highly populated countries is driving renewed interest in developing research and techniques to reduce global warming. The abundance of corn silk is a very important factor and needs to be considered when it comes to its utilization. Several studies have been conducted regarding the use of corn silk, namely as an ingredient for making low-fat, anti-obesity, anti-diabetic meatballs which are obtained from corn silk polysaccharides. However, the potential of corn silk as a raw material for fuel has not been studied. Therefore, it is important to conduct research to understand the potential of corn silk as a new and renewable energy source which is expected to become a long-term energy reserve. Thermogravimetric analysis of the characteristics and kinetics in the normal room temperature range of 900 oC under a nitrogen atmosphere at a heating rate of 40 oC/minute. The results show that the pyrolysis process of corn silk is divided into 3 stages related to the process of reducing the water content at a temperature of 65-130 °C, followed by the devolatilization stage at a temperature range of 216-506 oC and the last is a relatively slow decomposition up to 900 oC. The activation energy (Ea) in the active pyrolysis stage was calculated using the isoconventional fitting model using the Vyazovkin model. The resulting activation energy from the calculation of the Vyazovkin model is in the range of 215,522 kJ/mol each.